Hypoxia Conditioned Mesenchymal Stem Cell-Derived Extracellular Vesicles Induce Increased Vascular Tube Formation in vitro - Almeria, Ciarra; Weiss, René; Roy, Michelle; Tripisciano, Carla; Kasper, Cornelia; Weber, Viktoria; Egger, Dominik (Frontiers in Bioengineering and Biotechnology, 2019)
Mesenchymal stem/stromal cells (MSCs) display a variety of therapeutically relevant effects, such as the induction of angiogenesis, particularly under hypoxic conditions. It is generally recognized that MSCs exert their effects by secretion of paracrine factors and by stimulation of host cells. Furthermore, there is increasing evidence that some therapeutically relevant effects of MScs are mediated by MSC-derived extracellular vesicles (EVs). Since our current knowledge on MSC-derived EVs released under hypoxic conditions is very limited, we aimed to characterize MSC-derived EVs from normoxic vs. hypoxic conditions (5% O2). Adipose-derived MSCs were grown under normoxic and hypoxic conditions, and EVs were analyzed by flow cytometry using lactadherin as a marker for EVs exposing phosphatidylserine, CD63 and CD81 as EV markers, as well as CD73 and CD90 as MSC surface markers. Particle concentration and size distribution were measured by nanoparticle tracking analysis (NTA), and the EV surface antigen signature was characterized using bead-based multiplex flow cytometry. Furthermore, we evaluated the potential of MSC-derived EVs obtained under hypoxic conditions to support angiogenesis using an in vitro assay with an hTERT-immortalized human umbilical vein endothelial cell (HUVEC) line. Proliferation and viability of MSCs were increased under hypoxic conditions. EV concentration, size, and surface signature did not differ significantly between normoxic and hypoxic conditions, with the exception of CD44, which was significantly upregulated on normoxic EVs. EVs from hypoxic conditions exhibited increased tube formation as compared to normoxic EVs or to the corresponding supernatants from both groups, indicating that tube formation is facilitated by EVs rather than by soluble factors. In conclusion, hypoxia conditioned MSC-derived EVs appear to be functionally more potent than normoxic MSC-derived EVs regarding the induction of angiogenesis.